Cytokine-Induced Depression: Current Status and Novel Targets for Depression Therapy - Udina, Marc; Moreno-Espana, Jose; Capuron, Lucile; Navines, Ricard; Farre, Magi; Vieta, Eduard; Martin-Santos, Rocio (CNS & Neurological Disorders - Drug Targets, 2014)
Current treatments of depression include psychological, pharmacological and physical approaches. Pharmacological interventions to treat depression have previously focused on modifying dysfunctional neurotransmitter systems. Overall, these treatments have demonstrated an ability to manage major depression but otucomes continue to be poor in many patients, especially those with long term illness or with previous multiple relapses. This may be due to the fact that depression is a systemic and neuroprogressive illness involving multiple biological pathways such as immunological factors. There is substantial evidence that cytokine therapies induce depressive symptoms in clinical populations. The model of cytokine-induced depression has provided important information relative to the risk factors and biological pathways involved in the etiology of depressive symptoms and, most importantly, the identification and knowledge of these factors has allowed new treatment targets to be explored. When an exogenous cytokine such as interferon-alpha is administered, proinflammatory cytokines are activated, leading to alterations in neurotransmission and endocrine pathways and producing neurotoxicity. Several new treatments for depression acting through pathways other than amine neurotransmission have emerged in recent years. The regulation of the inflammatory response, the decrease in the activity of the hypothalamic-pituitary-adrenal axis and the prevention of neurotoxicity are potential targets for new drugs. Though these drugs are mostly at the proof-of-concept stage, some of them have already shown promising results for the treatment of depression.
Keywords: cytokines